Design The Stainless Steel Water Hose Pipe by using Flexible Spring - Rahman, Yusri; Fatimah binti Mohamed Yusop; Ts. MOHD SYAFIQ SYAZWAN BIN MUSTAFA (Progress in Engineering Application and Technology, 2021)
A clean toilet symbolizes a person's high personality. The importance of a clean toilet is to ensure that the toilet is comfortable to use and prevents the spread of germs and bacteria. Healthcare is one of the mandatory things for all communities in Malaysia. But still there are some people who take for granted in matters of hygiene in the bathroom. In addition, the use of dirty toilets can also lead to infections of the urinary tract or bladder which can be regarded as chronic. In addition, the use of unsystematic pipe hoses by leaving the hose on the bathroom floor and in the toilet hole is a matter that will cause dangerous diseases due to various germs and bacteria that will attack a person's body. It is because the pipe hose is not re-suspended in its proper place. Therefore, the study was applied stainless steel pipe hose using this flexible spring, the pipe hose will not fall to the floor again because the spring will return the pipe hose to its original place without the user placing the hose pipe back to the hose hanger. This study focused on only one bathroom in a private home. The test method that will be implemented is a pipe leak test and test the effectiveness of the pipe hose using the Quality Function Distribution (QFD) by being tested by 20 respondents by providing a survey form in the form of google forms. By using this system, , the purpose of this project is to ensure the cleanliness of the toilet is always kept away from bacteria by ensuring that toilet equipment such as plumbing is always in its original place without the user re-hanging the hose after using it and it is protected from all impurities.